An uncertain, erratic story: the pandemic in the UK. Issue 4 (16th November 2020) - Lapsley, Irvine
Abstract : Purpose: The purpose of this paper is to study the pandemic from the perspective of the UK health-care system and risk management. Design/methodology/approach: This paper follows a storytelling perspective. The author reflects on his experiences through the lens of research on health care and risk management. Findings: The impact of the pandemic has been so massive that it has challenged the capacity of the UKs National Health Service. The political influences at work have not always promoted best practice in risk management and indicate blame-avoidance strategies by politicians. Research limitations/implications: A single country experience of COVID-19. Practical implications: There are major issues of asset management, of delays in decision-making, of supply chain problems and the need to reform processes of handling of crisis management. Originality/value: This is an individual account of experiences of the pandemic.